2019
DOI: 10.1002/ijch.201900083
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly in Protein‐Based Bionanomaterials

Abstract: Supramolecular self‐assembled structures, based on protein−protein interactions, have garnered widespread interest as prospective functional bionanomaterials. Possessing unique properties, proteins have been widely investigated in the last years, due to their capability to form a diversity of natural and artificially designed zero‐, one‐, two‐ and three‐dimensional assemblies. These structures laid the basis for bionanomaterials design, including films, foams, gels, and others, with widespread applications in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 258 publications
(398 reference statements)
0
18
0
Order By: Relevance
“…Natural silks are produced by many insects and arthropods 4,5 . Notably, spider silk and silkworm silk have been the subject of much interest due to the former's incredible toughness and the latter's potential for genetic modification and commercial production [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Natural silks are produced by many insects and arthropods 4,5 . Notably, spider silk and silkworm silk have been the subject of much interest due to the former's incredible toughness and the latter's potential for genetic modification and commercial production [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Examples of such systems include full-length versions of proteins such as fused in sarcoma (FUS), other proteins from the FET family, and disordered prion-like domains (PLDs) excised from these and other systems. , Condensates can undergo hardening behavior over time through non-equilibrium transitions such as dynamical arrest and physical aging. Changes to material properties in condensates can also be realized through equilibrium solidification transitions and/or fibril formation, , wherein condensates serve as crucibles for driving equilibrium transitions. Mutations within PLDs of FUS and related proteins are associated with the formation of protein-rich deposits in the context of amyotrophic lateral sclerosis (ALS). ,,, McKnight and co-workers showed that archetypal PLDs from FUS and related proteins can form self-supporting hydrogels characterized by physically cross-linked fibrils. , Structural studies using peptide-based microcrystals led Hughes et al to propose that specific motifs known as low-complexity, aromatic-rich, kinked segments or LARKS provide the cohesive interactions to drive the formation of networks that scaffold peptide or protein-based hydrogels . These hydrogels are biochemical facsimiles of self-assembled fibrillar networks or SAFINS that are formed by synthetic associative polymers and proteins/peptides with or without low-molecular weight organic gelators. It is noteworthy that hydrogels and fibrils form above concentrations that are in the high micromolar to millimolar range. Patel et al, as well as Molliex et al, showed that systems such as the PLDs of FUS and hnRNPA1 and full-length hnRNPA1 can also undergo phase separation and percolation or the less nuanced liquid–liquid phase separation (LLPS) to form spherical, fluid-like condensates at bulk concentrations that are at least 1–2 orders of magnitude lower than the threshold concentrations for fibril formation.…”
mentioning
confidence: 99%
“…Excellent reviews have covered the topic of protein self-assembly and highlighted its broad reach across protein design and engineering, chemical and structural biology, bio- and nanotechnology, and materials science. , Our primary goal is not only to update those reviews with the most recent examples from the literature but also to provide a logical framework that we believe aptly describes the progression of the field from structure-building to property- and function-building. Although we acknowledge the key importance of disordered or heterogeneous protein ensembles, our focus here will be entirely on the design and construction of structurally well-defined, compositionally uniform protein assemblies, which lend themselves more readily to establishing design–structure–property–function relationships.…”
Section: Introductionmentioning
confidence: 99%